The Influence of Foliar Application with Proline Acid on Growth Parameters and Yield Component of Chamomile Plant (Matricaria chamomilla L.) Subjected to Water Stress - al-kazzaz, amel; Al-Saedi , abbas; Al-Saedi , hassan; Yahya, suhad; Abed , Rasha (Journal of Biotechnology Research Center, 2016)
A pots experiment was carried out in the green house of the green/ Botanical garden/ Department of Biology, College of Education for pure Science–Ibn–AL-Haithium/ Baghdad University, for the 2012-2013 growing season, to investigate the influence of foliar application of proline acid of three concentrations (50,100,150mg.L‾ˡ) and control on some growth and physiological parameters of chamomile plants subjected to water stress in three irrigations (3, 6 and 9days). The experiment was conducted as Completely Randomized Design (CRD) and three replications. Results indicated that effect of drought divergence from 3days to 9days reduced significantly the averages of plant growth parameters (plant height, concentration of nitrogen, phosphorus, calcium, biological yield, No. of flowering branches. pot‾ˡ, wt. of flowers. pot‾ˡ, and No. of flowers. pot‾ˡ). While exogenous application of proline acid had a positive effect on plant growth parameters and counteracted the adverse effect of water stress particularly 100mg.L‾ˡ proline acid concentration and the interval 9days on the growth parameters: plant height, phosphorus concentration, biological yield. Besides, the 150mg.L‾ˡ proline acid concentration counteracted the adverse effect of water stress through the interval 9days on the growth parameters: nitrogen, calcium concentrations No. of flowering branches.pot¯¹, wt. of flowers. pot‾ˡ and No. of flowers. pot‾ˡ.